2014
DOI: 10.1007/s12264-014-1473-9
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of dopamine D1 receptor phosphorylation at serine 421 attenuates cocaine-induced behaviors in mice

Abstract: Dopamine D1 receptors (D1Rs) play a key role in cocaine addiction, and multiple protein kinases such as GRKs, PKA, and PKC are involved in their phosphorylation. Recently, we reported that protein kinase D1 phosphorylates the D1R at S421 and promotes its membrane localization. Moreover, this phosphorylation of S421 is required for cocaineinduced behaviors in rats. In the present study, we generated transgenic mice over-expressing S421A-D1R in the forebrain. These transgenic mice showed reduced phospho-D1R (S42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, high expression of D1R, p-ERK1/2, and c-Fos immunoreactive products was not observed in the IC when treated with SCH23390 (D1R antagonist) and U0126 (a specific blocker of the ERK1/2 pathway). Previous studies on drug addiction and abuse [810] have shown that D1R plays a key role in cocaine, methamphetamine, and propofol addiction. SCH23390 and U0126 inhibit propofol self-administering behavior by reducing the expression of p-ERK1/2 in NAc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high expression of D1R, p-ERK1/2, and c-Fos immunoreactive products was not observed in the IC when treated with SCH23390 (D1R antagonist) and U0126 (a specific blocker of the ERK1/2 pathway). Previous studies on drug addiction and abuse [810] have shown that D1R plays a key role in cocaine, methamphetamine, and propofol addiction. SCH23390 and U0126 inhibit propofol self-administering behavior by reducing the expression of p-ERK1/2 in NAc.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that phosphorylation of extracellular-regulated protein kinase 1/2 (p-ERK1/2) can cause c-Fos to enter the nucleus and cause damage to cells [7]. Studies on drug addiction and abuse have shown that dopamine D1 receptor (D1R) plays a key role in cocaine, methamphetamine, and propofol addiction [8]. Also, the D1R antagonist SCH23390 inhibits propofol self-administration and decreases the expression of p-ERK1/2 in NAc [9].…”
Section: Introductionmentioning
confidence: 99%
“…Locomotor activity was measured in a Plexiglas chamber (AniLab, Ningbo, China) [22]. Each 8-beam infrared chamber (29 9 29 9 26 cm 3 ) was placed in an opaque sound-proof box equipped with exhaust fans.…”
Section: Methodsmentioning
confidence: 99%
“…In a separate study, NAC (60 mg/kg i.p.) Baculovirus-produced purified human recombinant protein Phospholipid-dependent kinase that plays multiple roles in signal transduction (Olive & Messing, 2004) Protein kinase C is involved in the desensitization of dopamine receptors (Zhang et al, 2014) and internalization of opioid receptors (Liu & Anand, 2001), which are involved in mediating the rewarding effects of drugs. Profilin (Fratelli et al, 2002) Human T lymphocytes Involved in the polymerization of globular actin into filamentous actin, and acts in association with microtubules to regulate structural plasticity (Nejedla et al, 2016) Synaptic plasticity is integral to drug-induced learning and behavior (Luscher, 2013) Sarco/ER calcium-ATPase (Viner et al, 1999) Sarocplasmic reticulum sourced from rabbit skeletal muscle Calcium pump involved in the sequestration of calcium ions in the endoplasmic reticulum thereby maintaining low cytosolic calcium levels (Kawamoto et al, 2012) An increase in postsynaptic calcium is a key mechanism in glutamatergic signaling, which is involved in addiction-related learning mechanisms (Tzschentke & Schmidt, 2003) Secretogranin III (Mullen et al, 2015) Human monocytic cells Neurotransmitter storage and transport Involved in neuropeptide Y release (Hotta et al, 2009) Stress induced phosphoprotein 1 (Fratelli et al, 2002) Human T lymphocytes Coordinates protein folding by and ATPase activity of HSP70 (Song & Masison, 2005) HSP70 in the nucleus accumbens has been implicated in the development of behavioral sensitization to morphine (Yang et al, 2014) Tyrosine hydroxylase (Borges et al, 2002) PC12 cells A rate-limiting enzyme in the synthesis of dopamine, which catalyzes the conversion of tyrosine into dihydroxyphenylalanine (Meiser et al, 2013) Dopamine plays a key role in the rewarding effects of drugs and mediates their incentive salience (Berridge & Robinson, 1998) Vesicular monoamine transporter 2 Mouse nucleus accumbens homogenate Vesicular trans (Baik, 2013) porter responsible for dopamine storage (Eiden & Weihe, 2011) Inhibition of vesicular monoamine transporter 2 reduces methamphetamine-induced dopamine release and decreases methamphetamine selfadministration (Beckmann et al, 2010) Vimentin (Fratelli et al, 2002) Human T lymphocytes Intermediate filament protein found in astrocytes …”
Section: Potential Therapies For Addiction May Influence Redox Statusmentioning
confidence: 99%